"Galicia Diplomática" (1882-1893): Image, Discourse and Identity. Origins of the Historicist Interpretation and Galician Identity Process in the Nineteenth-Century - Lorenzo Rodríguez, Abel (Madrygal. Revista de Estudios Gallegos, 2017)
The magazine Galicia Diplomática (1882-1893) is a reference in historical galician researchs. In this article we want show a part of its heritage, aims and influences which connected the magazine with identity process like the historicism of medievalism trough the heritage, documents and the debate with the industrial revolution or even with the laicist utilization or religious of what W. Benjamin called “body as emblema”.
Keywords: Historiography; Historical Heritage; Medievalism; Galeguism; Galicia Diplomática.